Determinação multiclasse de resíduos de medicamentos veterinários em músculo ovino por HPLC-FD e UHPLC-MS/MS - Bandeira, Nelson Miguel Grubel (2015)
The application of good livestock practices in the sheep industry is a growing concern on food security due to the increase of financial transactions in this sector in Brazil, mainly due to imports. To perform the monitoring Maximum Residue Limits (MRLs) are adopted such as suitable matrices for monitoring. The deposition of residues of veterinary drugs in sheep muscle is verified by appropriate analytical methods. In this work it were developed two methods aiming to determine avermectins residues in ovine muscle by HPLC-FD using QuEChERS method and also a method for the determination of different classes of veterinary drugs using UHPLC-MS / MS. The extraction was optimized by comparing the three most common variants of QuEChERS method and also the application of experimental design to select the best composition of the clean-up stage, varying amounts of PSA and C18. Some parameters such as derivatization step, the mobile phase composition, mobile phase flow, and the conditions of ionization source and ions entrance of the system were also optimized. The developed methods were validated by reference to Decision 657 of 2002 published by the European Community. The following parameters were evaluated: selectivity; linearity and working range; matrix effect; limits of detection and quantification; decision limit and detection capability; accuracy; and precision. The results were satisfactory, with the values of recovery in the concentration ranges required for each rated level, determination coefficients for curves prepared in solvent blank extract and white matrix were above 0.99 (except for ciprofloxacin) and linear working range was from 5 to 200 μg kg-1 for UHPLC-MS / MS and 2.5 to 112.5 μg kg-1 for HPLC-FD. There were no significant matrix effects only sulfamethoxazole, trichlorfon and albendazole by determining UHPLC-MS / MS. The limits of detection for HPLC-FD ranged from 4 to 18.4 μg kg-1 and decision limits from 10.7 to 59.4 μg kg-1 for UHPLC-MS / MS detection limits ranged from 1.7 to 33.3 μg kg-1 and for decision threshold from 5 to 100 μg kg-1. The method was considered suitable for routine analysis, and the confirmation was only possible using UHPLC-MS / MS, and the method was applied for determination of veterinary drug residues in sheep muscle in 11 samples by HPLC-FD and 36 UHPLC MS / MS